Perbedaan Kematangan Emosi Siswa Berdasarkan Keutuhan Keluarga - Mahfuza, Fitri; Nurfarhanah, Nurfarhanah (AHKAM, 2024)
This research was motivated by the fact that there were students SMA who were unable to control their emotions and channel them well, where students who, when emotional, immediately expressed their emotions without thinking about the consequences of these actions, apart from that, there were students who harbored feelings of anger so they experienced severe and excessive stress. This condition can trigger problems such as learning difficulties and deviant behavior. One of the influencing factors is the family environment. The objectives of this research are: (1) Describe the emotional maturity of students raised in intact families (2) Describe the emotional maturity of students raised in incomplete families (3) Describe the emotional maturity of students raised in intact families and non-intact families based on aspects ( 4) Test whether there is a significant difference between the emotional maturity of students raised by intact families and non-intact families. This research uses quantitative methods with a comparative study approach. The population in the study were students in class XII students 143 students, with the sample size being 112 students raised in intact families and 31 students raised in incomplete families, the sampling technique was total sampling technique. The instrument used in this research is an emotional maturity instrument with a Likert mode scale. The data analysis techniques used are descriptive analysis and hypothesis testing with the help of SPSS 20. The findings of this research show that: (1) The emotional maturity of students based on intact families is in the medium category, most students are able to manage emotions well. (2) The emotional maturity of students based on incomplete families is in the medium category, most students are able to manage emotions well. (3) There is a significant difference between the emotional maturity of students from intact families and students from non-intact families. This means that family integrity can also influence emotional maturity, where the emotional maturity of students from intact families is better than from non-intact families. Based on the results of this research, counselors can provide assistance to students through information services, individual counseling services and group counseling services.